O papel do subprojeto PIBID de Geografia da UFT/Araguaína para a formação de professores: - Soares, Amadeus Vieira (Universidade Federal do Tocantins, 2023)
This research aims to know the importance of the Institutional Program Initiation Grant to Teaching (PIBID) of the UFT Campus Geography in Araguaína in initial teacher training. The Geography of PIBID program had its first project in 2008 following the year 2015. The goal of the program is to offer encouragement and training of teachers for basic education, and enhance the teaching, encouraging students who choose teaching careers. These actions can contribute to improving the quality of education. The methodologies used were made through objective questions questionnaires which are geared to the use of methods that fellows develop within the classroom, this is the importance of geography PIBID, encourage the students to develop educational proposals that involves the student to think and develop the critical side. Survey data were collected through the questions and answer the questionnaires, records of the activities carried out by academics during their stay to PIBID of Geography program. The results indicate that the actions of Geography PIBID, developed by academics where nurture an important experience in the school environment, where the program combines dialogue and construction of knowledge about the educational process in the initial training of future teachers.